Insufficiency of Pro-heparin-binding Epidermal Growth Factor-like Growth Factor Shedding Enhances Hypoxic Cell Death in H9c2 Cardiomyoblasts via the Activation of Caspase-3 and c-Jun N-terminal Kinase - Uetani, Teruyoshi (American Society for Biochemistry and Molecular Biology, 2009)
Heparin-binding epidermal growth factor-like growth factor (HB-EGF) is a cardiogenic and cardiohypertrophic growth factor. ProHB-EGF, a product of the Hb-egf gene and the precursor of HB-EGF, is anchored to the plasma membrane. Its ectodomain region is shed by a disintegrin and metalloproteases (ADAMs) when activated by various stimulations. It has been reported that an uncleavable mutant of Hb-egf, uc-Hb-egf, produces uc-proHB-EGF, which is not cleaved by ADAMs and causes dilation of the heart in knock-in mice. This suggests that the shedding of proHB-EGF is essential for the development and survival of cardiomyocytes: however, the molecular mechanism involved has remained unclear. In this study, we investigated the relationship between uc-proHB-EGF expression and cardiomyocyte survival. Human uc-proHB-EGF was adenovirally introduced into the rat cardiomyoblast cell line H9c2, and the cells were cultured under normoxic and hypoxic conditions. Uc-proHB-EGF-expressing H9c2 cells underwent apoptosis under normoxic conditions, which distinctly increased under hypoxic conditions. Furthermore, we observed an increased Caspase-3 activity, reactive oxygen species accumulation, and an increased c-Jun N-terminal kinase (JNK) activity in the uc-proHB-EGF-expressing H9c2 cells. Treatment of the uc-proHB-EGF transfectants with inhibitors of Caspase-3, reactive oxygen species, and JNK, namely, Z-VAD-fmk, N-acetylcysteine, and SP600125, respectively, significantly reduced hypoxic cell death. These data indicate that insufficiency of proHB-EGF shedding under hypoxic stress leads to cardiomyocyte apoptosis via Caspase-3- and JNK-dependent pathways.